The twelve topsy-turvy, very messy days of Christmas - Patterson, James, 1947-; Safran, Tad (2022)
During the holiday season, a family of three, missing someone very dear to them, find their house filling up with unexpected guests, making Christmas memories to last a lifetime.
After their mother's death on Christmas Day five years ago, Will and Ella Sullivan, and their father, Henry, come to a family agreement: Christmas is a holiday for other people. At their brownstone in Harlem, stockings go unstuffed, tinsel unstrewn, gifts unbought, mistletoe unhung, chestnuts unroasted, carols unplayed, cookies uncooked, a tree un-visible, and guests uninvited. Until this year. Until guests start arriving anyway. In pairs and sixes, in sevens and tens-- they keep coming. And they stay. For twelve long, hard, topsy-turvy, very messy days. That's when the Sullivans discover that those moments in life that defy hope, expectation, or even imagination, might be the best gifts of all. -- adapted from Goodreads and perusal of book
Keywords: Bereavement -- Fiction; Entertaining -- Fiction; Harlem (New York, N.Y.) -- Fiction; Christmas fiction; Domestic fiction; Novels